Development Pineapple Distribution Channel of Farmers in Nong Phan Chan Sub-district - Chotklang, Atchareeya; Saikeow, Shupakeae (WMS Journal of Management, 2020)
The objectives of this study were to 1) study the relationship of members in the distribution channels, 2) analyze the distribution channels and 3) develop distribution channels for pineapple products for consumption. In–depth interview was employed with pineapple producers and pineapple stall. Group discussion was carried out with government agencies. And the quantitative data were collected by using questionnaire conducted with 400 consumers, selected by accidental sampling. The qualitative data were analyzed by using content analysis, whereas the quantitative data were analyzed by computing percentage, mean, and S.D. The research results were as follows: 1) the relationship of members in the pineapple distribution channel for consumption was a system that was familiar to relatives and friends. As for pineapple for factory delivery, this had business status. 2) pineapple distribution channels for consumption were analyzed. The strength was selling products throughout the year whereas the weakness was the middleman. There was a limit on the number of purchases and the opportunity was that the government had registered the GI for pineapples. However, there were obstacles from the sale of pineapples that were not up to the quality standard and 3)the attractiveness of the website with an interesting main screen and participation in fairs could stimulate buying decisions. For suggestions, the selection of a distribution channel should take into account the target group, with the advantages and disadvantages for each method